Peran Notaris dalam Penyelesaian Perselisihan Terhadap Akta Perjanjian Pengikatan Jual Beli (PPJB) Yang Dibuat Para Pihak Dihadapannya - Mutia Sari, Dwi; Azheri, Busyra; Elvardi, Jean (Universitas Ekasakti, 2023)
The main task of a notary is to create or record events authentically. For parties who make an agreement before a Notary, if a dispute arises related to the deed, then usually the first person to ask for advice is the Notary concerned. The main problem in this research is how the notary plays the role of the peace settlement agreement carried out by the parties before the notary regarding the dispute over the Deed of Jual Beili Peingikatan Agreement (PPJB). This legal research uses an empirical juridical method, namely a method of approaching problems by looking at applicable legal norms and then connecting them with legal facts found in the field. Meanwhile, this type of research is descriptive analytical, namely providing a clear and detailed description of an event that occurred. The results of the research, the role of a notary in the selection process of the Deed of Juial Beili Agreement (PPJB) made by the parties in front of him is that the notary can act by providing input regarding disputes between the parties in the deed made by the notary. This function is the role of the notary voluntarily as a party. who understands his duties and functions as a notary, and in this case the notary is also considered to really understand the essence of the ongoing problems and the peace litigation carried out by the parties before the notary regarding disputes over the Deed of Juial Beili Peining Agreement (PPJB), namely that the notary has the same ideals. Intuitive signatures provide legal guidance as well as providing information related to the execution of authentic deeds, as stipulated in Article 15 Paragraph (2) huiruif eiUiUiJN. In this case, the notary provides legal counseling to make the next deed after the parties have reconciled, namely in the form of a peace deed accompanied by a power of sale deed.